Hold the Meat but Pass the Disgust: Disgust as an Instrumental Negative Emotion - Somerville, Annie (Wake Forest University, 2021)
People upregulate negative emotions when those emotions are instrumental to goal attainment (Tamir & Ford, 2009). Vegetarian diets are increasingly popular food goals that address moral, health, and environmental concerns associated with meat-eating. Therefore, we examined whether and how disgust toward meat is instrumental to vegetarian diet goals. We conducted two studies: one longitudinal and one experimental. In the longitudinal study, we predicted that experience of vegetarians would affect their disgust toward meat, as newer vegetarians might need to recruit more disgust than more experienced vegetarians whose vegetarian behaviors are likely more automatic. We found that both newer and more experienced vegetarians had higher disgust toward meat. Additionally, we found that throughout the course of the study, average vegetarians/reduced meat consumers experienced an increase in meat disgust followed by a decrease. However, time since quitting/reducing meat did not moderate the relationship between time and disgust toward meat. The experimental study tested whether vegetarians would willingly upregulate disgust during potential meat temptations. We predicted that vegetarians rating meat dishes would prefer to focus on disgusting versus appetizing aspects of the dishes. Indeed, we found that vegetarians preferred disgust when faced with meat temptations. However, vegetarians did not endorse the meta-emotion belief that disgust is useful to goal pursuit more than non-vegetarians. Our research suggests that disgust is an instrumental, negative emotion to vegetarian, vegan, and reduced-meat diets. Even more, people are motivated to leverage disgust, although subconsciously, when tempted with meat.
Keywords: disgust; goals; negative emotions; vegetarians